Effects of Mindfulness-Based Interventions on Burnout: A Systematic Review - Lena Marianti; Badeni Badeni; Eko Risdianto (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2026)
Burnout is characterized by emotional exhaustion, depersonalization or cynicism, and reduced personal accomplishment and may develop following prolonged exposure to occupational or academic stress. Mindfulness-based interventions have increasingly been examined as an approach to preventing or reducing burnout. However, recent evidence remains fragmented across professional and educational populations, and the consistency of findings and proposed pathways underlying their effects have not been clearly synthesized. This systematic review aimed to evaluate evidence published between 2020 and 2025 on the use of mindfulness-based interventions to address burnout. A literature search was conducted in Scopus using predefined eligibility criteria, including publication within the specified period and explicit examination of a mindfulness-based approach in relation to burnout. Of the 164 records identified, 11 studies met the inclusion criteria and were included in the review. Overall, the included studies generally reported reductions in burnout following mindfulness-based interventions, particularly among health professionals, educators, and students. The findings also suggested that increased present-moment awareness, improved emotion regulation, and nonjudgmental acceptance may contribute to these outcomes, although these pathways were not consistently tested across studies. The available evidence supports the potential use of mindfulness-based programs as preventive or supportive strategies for burnout. Nevertheless, variation in study designs, populations, intervention formats, and outcome measures limits firm conclusions. Further rigorous studies are needed to determine which intervention components are most effective, for whom, and under what conditions.